Technological strategies and spatial organization the uttermost part of South America during Late Holocene: a use-wear approach - Alvarez, Myrian Rosa (2018)
During Late Holocene the south-eastern Atlantic coast of Tierra del Fuego (Argentina) was inhabited by hunter-gatherer-fisher societies who exploited marine resources as well as a wide range of lithic and bone raw-materials to produce different tool designs. Most of the archaeological sites are shell middens, of varying sizes and extent, made up frequently of limpets (Nacella sp.) and mussels (Mytilus sp.). These sites exhibit a remarkable diversity in relation to the formation processes, the zooarchaeological record, tool designs and assemblage composition.The general aim of this presentation is to explore the possible sources of this archaeological variability focusing on the consumption strategies developed by these coastal societies. To accomplish this objective use-wear analysis of lithic and bone tools were undertaken for two reasons: to identify the activities carried out on the settlements and the resources exploited and to unveil labour processes in which tools were employed to explore in a second instance, which morpho-technical traits were selected to perform different working processes.